Duplex-phlebography correlation in the limb venous mapping superiors for the realization of fistulas arteriovenous for hemodialysis - Esperón, Alejandro; López Chapuis, Daniel; Sciuto, Fernando; Vallverdú, Martín; Garrido, Pedro; Curi, Jorge (Cirugía del Uruguay, 1995)
When clínica/ evaluation is not enough, the evaluation of the venous candi/ion of /he upper limbs far the realiza/ion of angioaccess far hemodialysis is classically based on phlebography, an invasive, risky method. The appearance of non invasive techniques such as ecoDoppler (duplex) makes it necessary to do research in arder to determine the utility of the method and define its indications. The authors analyse 35 venous mappings of the upper limbs by phlebography and duplex and compare its results far /he different venous regions. They come to the conclusion that duplex presented the best performance far /he humero-axillary-subc/avian regían, detecting thrombosis with a sensitivity of 100%, a specificity of 97%, positive predictive value of 50% and negative predictive va/ue of 100%. Far superficial axis (radial and superficial ulnar, basilic and cephalic) there is low sensitivity far the determina/ion of presence and permeability of the axis but 100% specificity. Duplex was no/ use ful far the description of veins in arder to determine utility far AVF Final/y, the authors make recomendations as regards indications of these paraclinical tests.